Computer Programming for Absolute Beginners - Wassberg, Joakim (Packt Publishing, 2020)
Get to grips with the building blocks of programming languages and get started on your programming journey without a computer science degree Key Features Understand the fundamentals of a computer program and apply the concepts you learn to different programming languages Gain the confidence to write your first computer program Explore tips, techniques, and best practices to start coding like a professional programmer Book Description Learning how to code has many advantages, and gaining the right programming skills can have a massive impact on what you can do with your current skill set and the way you advance in your career. This book will be your guide to learning computer programming easily, helping you overcome the difficulties in understanding the major constructs in any mainstream programming language. Computer Programming for Absolute Beginners starts by taking you through the building blocks of any programming language with thorough explanations and relevant examples in pseudocode. You'll understand the relationship between computer programs and programming languages and how code is executed on the computer. The book then focuses on the different types of applications that you can create with your programming knowledge. You'll delve into programming constructs, learning all about statements, operators, variables, and data types. As you advance, you'll see how to control the flow of your programs using control structures and reuse your code using functions. Finally, you'll explore best practices that will help you write code like a pro. By the end of this book, you'll be prepared to learn any programming language and take control of your career by adding coding to your skill set. What you will learn Get to grips with basic programming language concepts such as variables, loops, selection and functions Understand what a program is and how the computer executes it Explore different programming languages and learn about the relationship between source code and executable code Solve problems using various paradigms such as procedural programming, object oriented programming, and functional programming Write high-quality code using several coding conventions and best practices Become well-versed with how to track and fix bugs in your programs Who this book is for This book is for beginners who have never programmed before and are looking to enter the world of programming. This includes anyone who is about to start studying programming and wa...
Title from content provider.
Keywords: Computer programming.; elektronické knihy; electronic books